Analisis Jenis Kalimat dalam Teks Negosiasi pada Buku Siswa Kelas X SMA - Julia Phonna; Ridwan Ibrahim; Azwardi Azwardi (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
The title of this research is the Analysis of Sentence Types in Negotiation Text in Class X SMA Student Book. The formulation of the research problem is to describe the types of sentences based on the content in the negotiating text in the Indonesian language textbooks for class X SMA students. This study aims to describe the types of sentences based on their contents in the negotiating text in the Indonesian language textbooks for class X SMA students. This research is useful for researchers, teachers, and students. For researchers, this research is useful to add insight. For teachers, this research is useful for reviewing lesson planning, and for students it is useful for input in understanding the types of sentences in the negotiation text. This research method uses a qualitative approach with descriptive research type. The research data is in the form of sentences in 4 negotiation texts. The data sources of this study were 4 negotiation texts in Indonesian language textbooks for class X SMA students. The data was collected by reading the negotiation text, sorting the number of sentences in each text, marking the order of the parts of the negotiation text that describe the types of sentences based on their content, and classifying the data into tables. The analysis technique used in this research is qualitative analysis techniques. The results showed that there were 4 types of sentences based on their contents in 4 negotiating texts, including (1) declarative sentences, (2) imperative sentences, (3) interrogative sentences, and (4) exclamative sentences. Negotiation text 1 HP Recently found 6 declarative sentences, 2 imperative sentences, and 3 interrogative sentences. The negotiation text 2 Thank You Mrs. Mia found 7 declarative sentences, 4 imperative sentences, 5 interrogative sentences, and 1 exclamative sentence. Negotiation text 3 Ladzidzan Ice Cream Bakery found only 5 declarative sentences. Negotiation text 4 Citizen Negotiation with Investor found 8 declarative sentences, 1 imperative sentence, and 4 interrogative sentences